The Effect of CaO Weight from Snail Shell (Pilla Ampullacea) On Its Activity As Heterogeneous Catalyst on Biodiesel Conversion Of Bran Oil - Hikmah Fatmawati; Wellyana Puspitasari; Rohini Pujiarti; Sesy Ardyanti; Is Fatimah (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
Research on utilization of snail (Pilla ampullacea) shell as CaO source for biodiesel conversion from rice bran oil has been investigated. CaO was derived by calcining the shell at pada 900oC for 2 h. The powder obtained from the process was characterized using x-ray diffraction (XRD), energy dispersive x-ray (EDX), Fourier-Transform Infra-red (FTIR) and surface basicity test. In order to test the activity of catalyst, effect of catalyst weight on the yield of conversion as studied. Results show that the derived material is composed from dominantly CaO and the material demonstrates activity in rice bran conversion into biodiesel. Compared to NaOH, the CaO catalyst exhibits more effectively active as shown by the higher yield. From varied catalyst weight, it is obtained that at the range of 2.5-10% catalyst weight does not affect significantly to the increasing yield.